Principles for Determining the Costs of Professional Development for School Leaders - McCauley, Carlas (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2025)
Professional development (PD) is a central component of school improvement, yet much of the literature on PD spending focuses on teachers. Despite the substantial resources allocated to PD, little is known about the corresponding investments made in school leaders. This article reviews the research on teacher PD spending and uses those insights to develop a set of principles for school leaders. It also addresses the current gap in evidence about PD spending for school leaders by offering guidance on how to capture and assess those expenditures.